CoMoO4 and Ni1/3Co2/3MoO4 nanosheets with high performance supercapacitor and nonenzymatic glucose detection properties. Issue 103 (6th October 2015) - Zhang, Jingchao; Zhang, Renchun; Song, Pingping; Zhao, Jingli; Guo, Xueying; Zhang, Daojun; Yuan, Baiqing
Abstract : Novel CoMoO4 and Ni1/3 Co2/3 MoO4 nanosheets were synthesized by a time-saving solvothermal method, and exhibited excellent supercapacitor properties and electrocatalytic activity towards glucose oxidation. Abstract : Novel CoMoO4 and Ni1/3 Co2/3 MoO4 nanosheets were synthesized by a time-saving solvothermal method with medium conditions, and characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and high-resolution TEM (HRTEM). Enhanced specific capacitance (1032.39 F g −1 at 4 A g −1 ) and good cycle stability (remaining 85.18% at after 1000 cycles) are observed in aqueous KOH electrolytes of Ni1/3 Co2/3 MoO4 nanosheets, which could be ascribed to the high charge accommodation, small ion-transport resistance, and good electrical conductivity of the ultrathin nanosheet structure. In addition, the as-prepared CoMoO4 nanosheets exhibited good electrocatalytic activity toward the oxidation of glucose.